Excision of Recurrent Hemangioma in Hand with Reconstruction Using Abdominal Flap - Tua, Ivan Joalsen Mangara; Ardan, Andi Mohammad; Pagehgiri, Hari Daswin; Sukamto, Amy Rosalie; Dwipayana, Made Angga Putra (Folia Medica Indonesiana, 2022)
Highlights: • Hemangioma of the hand is a challenging case due to the need to maximize eradication of the mass while minimizing damage to the healthy tissue to preserve the physiologic function of the hand. • The reconstruction of the defect also needs to be taken into account to maintain the cosmetical appearance. • Collaborative multidisciplinary work is essential to achieve these demands and maintain the patient's quality of life. Abstract: Hemangiomas are known for their typical involution with age. However, around 40% of cases require intervention. Hemangioma in hand is challenging because the hand function and the aesthetic appearance need to be preserved. Hereby we reported a 21-year-old woman with a recurrent hemangioma on the left hand in Abdul Wahab Sjahranie Hospital, Samarinda, Indonesia. The patient's previous surgery was ineffective since the mass reappeared in the same area. We performed surgical excision and reconstruction with an abdominal flap. One-month and one-year postoperative follow-up indicated good flap viability and preserved hand functions without the need for amputation. This report also emphasizes the importance of collaboration from multiple surgical and medical fields to allow favorable outcomes in this case.